2017
DOI: 10.1016/j.bjm.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of methicillin-resistant Staphylococcus aureus isolated from blood in Rio de Janeiro displaying susceptibility profiles to non-β-lactam antibiotics

Abstract: The distinction between healthcare-associated MRSA (HA-MRSA) and community-associated MRSA (CA-MRSA) infections has become increasingly blurred. We assessed the molecular characterization and antimicrobial resistance profile for MRSA isolates from blood. Most of all (81.9%) isolates are related to known HA-MRSA and CA-MRSA epidemic lineages, such as, USA300, USA400, USA600, USA800 and USA1100. This is the first multicenter study in Rio de Janeiro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
4
13
4
Order By: Relevance
“…In this study, we also described for the first time in Paraguay the CC5-ST100-IV-t002 clone closely related to the Argentinian pediatric clone [35]. Moreover, two other minor clones were also identified: CC30-ST435-IV-t021-PVL positive and CC8-ST72-IV-t148, both reported previously in other countries of the region such as Argentina, Brazil, and Uruguay [6,7,28,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we also described for the first time in Paraguay the CC5-ST100-IV-t002 clone closely related to the Argentinian pediatric clone [35]. Moreover, two other minor clones were also identified: CC30-ST435-IV-t021-PVL positive and CC8-ST72-IV-t148, both reported previously in other countries of the region such as Argentina, Brazil, and Uruguay [6,7,28,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 76%
“…In the Republic of Korea, Chung et al (2008) also found a predominance of SCCmec IV (68.7 %) among MRSA isolated from AD children. Further, SCCmec IV is commonly found in community isolates in Rio de Janeiro, Brazil [18], which coincides with our results. In addition, genotypic characterization of isolates showed that over 90 % of the S. aureus isolates analysed belonged to the USA400/ ST1, USA800/ST5 and USA1100/ST30 genotypes, the most commonly lineages found in our country [18,19].…”
supporting
confidence: 92%
“…Further, SCCmec IV is commonly found in community isolates in Rio de Janeiro, Brazil [18], which coincides with our results. In addition, genotypic characterization of isolates showed that over 90 % of the S. aureus isolates analysed belonged to the USA400/ ST1, USA800/ST5 and USA1100/ST30 genotypes, the most commonly lineages found in our country [18,19]. A study conducted by our group with AD children colonized/infected by S. Aureus showed that more than 50 % of the isolates belonged to one of these three lineages [17].…”
supporting
confidence: 92%
“…The predominant MSSA strains characterized in the present study (ST1635-CC5 and ST30) were frequently detected in epidemiologic studies in Brazil 17,18 . Among MRSA strains, those with SCCmec type II related to worldwide epidemic clones such as USA100 (NY/J) were prevalent.…”
Section: Discussionmentioning
confidence: 49%
“…The results of molecular typing of S. aureus strains demonstrate a great diversity in clones circulating in this hospital environment, as all sequence types identified were associated with the important clonal complexes circulating in the American continent (i.e., CC5, CC8, CC45, and CC30). Furthermore, the majority of the strains isolated were related to worldwide epidemic clones such as USA100 (NY/J), USA300, and USA600 16,17 .…”
Section: Discussionmentioning
confidence: 99%